Optimization of sorbitol, glycerol, and propyleneglycol mixture in sunscreen gel of ethanolic extract of Curcuma mangga - Yuliani, Sri Hartati Hartati (INDONESIAN JOURNAL OF PHARMACY, 2010)
The research about optimization of sorbytol, glycerol, and propyleneglycol mixture  in  sunscreen  gel  of  ethanolic  extract  of  Curcuma  mangga has  been done.  The  aims  of  this  research  was  to  discover  the optimum  mixture  of sorbytol,  glycerol  and  propyleneglycol  that  gave  good  physycal  characteristic  of the  gel.  First, made the ethanolic extract of Curcuma mangga as active ingredient.  The SPF value of the ethanolic extract of Curcuma mangga was measured.  Simplex  lattice  design  was  employed  to  create  the  optimum composition  of  sorbitol,  glycerol  and  propyleneglycol  in  the  sunscreen  gel. Physical characteristic of the gel including spreadability, viscosity and the alteration of the gel viscosity was measured. The result showed that there were optimum composition between sorbytol, glycerol and propyleneglycol which gave good  physical  characteristics  based  on  the  shading  area  at  the  counterplot superimposed.Keywords: sorbitol, glycerol, propyleneglycol, Curcuma mangga, sunscreen gel